Ixazomib combined with lenalidomide and dexamethasone chemotherapy for newly diagnosed multiple myeloma in China—Compared with bortezomib/lenalidomide/dexamethasone - Zhongjun Huo; Fang Chen; Ping Liu; Zimian Luo (Cancer Medicine)
Abstract Background To compare the response and safety of Ixazomib/Lenalidomide/Dexamethasone (IRd) and Bortezomib/Lenalidomide/Dexamethasone (VRd) treatment in newly diagnosed multiple myeloma (MM). Methods This was a single‐center retrospective analysis in Xiangtan Central Hospital. A total of 52 newly diagnosed MM patients from June 2019 to June 2021 were enrolled and divided into the IRd (n = 21) and VRd (n = 31) groups. After 4 cycles of chemotherapy, the best response and adverse events were recorded. Moreover, the progression‐free survival (PFS) and overall survival (OS) were calculated. Results Patients in IRd group and VRd group showed similar PFS (Log‐rank p = 0.70), OS (Log‐rank p = 0.61) and overall response rate (83.87% vs 90.48%, p = 0.803). In addition, patients in VRd group showed lower Eastern Cooperative Oncology Group scores (p = 0.047), and higher incidence of peripheral sensory neuropathy (0.00% vs 19.35%, p = 0.032) than that of patients in IRd group. Conclusion Compared to VRd regimen, IRd had the similar efficacy, better safety, and may be more convenient for patients with poor basic condition for newly diagnosed MM. This study provides an insight for physicians to use IRd as first‐line treatment in MM.